2023
DOI: 10.4143/crt.2022.1557
|View full text |Cite
|
Sign up to set email alerts
|

Early Plasma Circulating Tumor DNA as a Potential Biomarker of Disease Recurrence in Non-metastatic Prostate Cancer

Abstract: In non-metastatic prostate cancer (nmPCa) setting, it is important to early identify the patients at risk of biochemical recurrence (BCR) for immediate postoperative intervention. Our study aimed to evaluate the potential clinical utility of circulating tumor DNA (ctDNA) for predicting disease recurrence. Materials and MethodsThis real-world observational study evaluated 161 cases of nmPCa undergoing next-generation sequencing at our institution. A total of 139 ctDNA samples and 31 biopsied tumor tissue underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Thus, using the example of patients with colorectal cancer, the potential clinical significance of ctDNA determination was shown for the first time. ctDNA can be found in many types of cancer, including BC [79], lung cancer [80], colorectal cancer [81], prostate cancer [82], gastric cancer [83], ovarian cancer [84], and others [85][86][87][88][89]. It has also been shown that ctDNA can be detected in early-stage cancer patients, while the most characteristic change in cancer patients is DNA hypermethylation.…”
Section: Possible Applications Of Ctdna In Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, using the example of patients with colorectal cancer, the potential clinical significance of ctDNA determination was shown for the first time. ctDNA can be found in many types of cancer, including BC [79], lung cancer [80], colorectal cancer [81], prostate cancer [82], gastric cancer [83], ovarian cancer [84], and others [85][86][87][88][89]. It has also been shown that ctDNA can be detected in early-stage cancer patients, while the most characteristic change in cancer patients is DNA hypermethylation.…”
Section: Possible Applications Of Ctdna In Oncologymentioning
confidence: 99%
“…Most of these studies have been carried out on lung cancer [80,[99][100][101][102] and colorectal cancer [81,103], including the use of DNA methylation analysis [104]. However, other types of cancer, such as ovarian cancer [84], prostate cancer [82,105], pancreatic ductal adenocarcinoma [106], melanoma [107], and others [88,89,[108][109][110], have also been widely represented in the works carried out in recent years.…”
Section: Possible Applications Of Ctdna In Oncologymentioning
confidence: 99%